Computational study of glucosepane–water and hydrogen bond formation: an electron topology and orbital analysis. Issue 5 (4th April 2017) - Nash, Anthony; Saßmannshausen, Jörg; Bozec, Laurent; Birch, Helen L.; de Leeuw, Nora H.
Abstract : The collagen protein provides tensile strength to the extracellular matrix in addition to localising cells, proteins and protein cofactors. Collagen is susceptible to a build up of glycation modifications as a result of an exceptionally long half-life. Glucosepane is a collagen cross-linking advanced glycation end product; the structural and mechanical effects of glucosepane are still the subjects of much debate. With the prospect of an ageing population, the management and treatment of age-related diseases is becoming a pressing concern. One area of interest is the isolation of hydrated glucosepane, which has yet to be reported at an atomistic level. This study presents a series of glucosepane–water complexes within an implicit aqueous environment. Electronic structure calculations were performed using density functional theory and a high level basis set. Hydrogen bonds between glucosepane and explicit water were identified by monitoring changes to covalent bonds, calculating levels of electron donation from Natural Bonding Orbital analysis and the detection of bond critical points. Hydrogen bond strength was calculated using second-order perturbation calculations. The combined results suggest that glucosepane is very hydrophilic, with the imidazole feature being energetically more attractive to water than either hydroxyl group, although all hydrogen bonds, regardless of bond strength, were electrostatic in nature. Our results are in growing support of an earlier hypothesis that cross-links may result in an increase in interstitial water retention, which would permit the collagen fibril to swell, thereby potentially affecting the tensile and compression properties and biological function of connective tissues.